Factors influencing development of residual stresses during crystallization firing in a novel lithium silicate glass-ceramic - Wendler, Michael; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2019)
Objective: Development of residual stresses is a potential source of premature fractures in glassy materials, being of special interest in novel lithium silicate glass-ceramics that require a crystallization firing to achieve their final mechanical properties. The aim of this work was to assess the influence of various firing tray systems and the application of different cooling protocols on the development of residual stresses in Suprinity PC crowns. Their effect on the in vitro lifetime of the restorations was also studied. Methods: Thirty crowns were milled out of Suprinity PC blocks and crystallized using one of five different commercial firing tray systems (n = 6). Samples in each group were cooled following a fast (FC = 5.5 °C/s), a slow (SC = 0.4 °C/s)or the manufacturer's reference cooling (REF). Obtained crowns were sagittally or transversally sectioned and the magnitude and distribution of residual stresses was determined using the light birefringence method. Extra crowns of three of the subgroups (n = 8)were produced and submitted to chewing simulation for 10 6 cycles or until fracture ensued. Results: Average residual stresses ranged between 0 and 1.5 MPa (peaks of 5 MPa). Highest stress magnitudes were observed at the support areas of groups using firing pins, leading to thermal cracks in FC samples and premature failures in the REF subgroup. The use of fibrous pads and firing pastes limited the development of residual stresses, whereas application of SC regimes extended the lifetime of the restorations. Significance: Development of residual stresses during crystallization firing in lithium silicate glass-ceramics results critical for their mechanical performance and should be therefore avoided by ensuring a homogenous cooling of the structures.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Cooling protocol; Crystallization; Firing tray; Glass-ceramic; Lifetime; Lithium silicate; Residual stress